EFL faculty members' research engagement: voices from Iran. Issue 1 (2nd January 2019) - Farsani, Mohammad Amini; Babaii, Esmat
ABSTRACT: This nationwide study examines the English as a Foreign Language (EFL) faculty members' engagement in and with research in a major site of EFL context by surveying a representative sample of 140 faculty members. Further, the correlation between the respondents' levels of engagement in and with research and their demographic features concerning academic position and years of experience was investigated. Our findings demonstrate the respondents' high levels of engagement with reading research and engagement in doing research in several aspects. Furthermore, the reasons for reading and doing research were discussed. The findings of the study point to a number of institutional, procedural, instrumental facilitators and suppressors to research engagements. Interestingly, the EFL faculty members perceived a significant gap between their expectations of, and management support for, doing research. Finally, pedagogical implications of the nature of the engagement are discussed.